THEOLOGY OF PEACE: AN ANALYSIS FROM ISLAMIC PERSPECTIVE - Islam, Tazul (International Prophetic Conference (SWAN) FPQS USIM, 2022)
This study aims at exploring the Islamic theology of peace. This requires investigating peaceful Nature and Will of God, His peace seeking instruction, His peace circle, Quranic perspective of violence, motives behind approving violence, divine solutions to end violence, peace in terms of goals and means; man’s Inner peace and his peace seeking behaviour towards others. This study is qualitative in nature which follows a discourse analysis method to deal with the peace related narratives in Islamic orthodox sources namely the Quran and the Prophetic Narrations (sunnah). In addition, a new analytical tool called ‘Islamic goal-based (maqasid) approach’ will also be used to develop a new peace building framework from the Islamic perspective.